International Commercial Arbitration as a Mechanism to Activate Legal Security for Investment in Algeria - Boudaoud, Khelifa; Meguireche, Mohamed (Journal of Legal Studies and Researches, 2023)
To encourage foreign investments as one of the basic mechanisms for achieving economic growth and prosperity, the Algerian legislator stipulated a guarantee that is considered the most appropriate and fastest for the foreign investor, represented in arbitration. International trade, as an alternative mechanism to the judiciary, embodied in domestic laws and international agreements alike, in an effort to achieve legal security.